Agronomic performance of five tropical grasses under grazing in the "cerrado" region - Thomas, D.; Andrade, R. P. de (Pesquisa Agropecuaria Brasileira, 2014)
An experiment was conducted over four seasons at the Centro de Pesquisa Agropecuária dos Cerrados (CPAC/EMBRAPA), Planaltina, Brasília, DF, Brazil, in a tropical savanna (cerrado) environment to compare the agronomic performance under grazing of five grasses: Andropogon gayanus cv. Planaltina, Brachiaria decumbens cv. Basilisk, B. ruziziensis, B. humidicola and Panicum maximum cv. Guinezinho. Grasses were sown with or without Stylosanthes guianensis cv. Cook. The productivity of A. gayanus remained remarkably constant in the three years following the establishment year whilst that of the other grasses declined markedly. B. humidicola was the least productive. In the first season following the establishment year the dry matter yields, dry matter digestibilities in vitro, N, Ca and P contents were higher in the plots containing legume than in the pure grass plots. At the beginning of the second season after the establishment year, S. guianensis disappeared because of anthracnose. However, there was a pronounced residual effect of the legume in that season in plots formerly containing legume, and both N contents and N yields of the grass were appreciably increased.